COLLECTIVE EMPOWERMENT IN LATIN AMERICA - Otero, Gerardo. ([S.l.])
1 online resource
Keywords: This book develops a theory of collective empowerment that looks for change both from the bottom up, in civil society, and from the top down, from state interventions responding to such pressure. Reflecting on the advancement of Indigenous and peasant movements in Latin America since the neoliberal reformation of capitalism in the 1980s, the book outlines a path for progressive social action in which bottom-up pressure by social movements can help progressive parties to gain state power. The book considers how Indigenous and peasant movements in Argentina, Bolivia, Brazil, Ecuador, and Mexico have tried to reshape crucial structures of society from the bottom up. While this mobilization from below is critical and necessary, the book argues that these movements must be supplemented by top-down change from progressive state interventions, as happened mostly in Bolivia and Brazil. The authors conclude that progressive societal action can have massive impact in transforming some of the main socioeconomic structures that determine humans' relation to the extraction of natural resources, income and wealth inequality, and even the location of a nation's insertion in world capitalism. This book will be an important resource for social-movement activists and for researchers working in political sociology, sociological theory, political studies, development studies, social movements, and Latin American Studies.